2015
DOI: 10.1186/s12885-015-1638-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of a minimal intervention for sexual concerns after cancer: a comparison of self-help and professionally delivered modalities

Abstract: BackgroundInformation and discussion of sexual changes with a health professional is a high priority for many cancer patients in order to assist with sexual changes and ensure that sexual intimacy does not cease post-cancer. The PLISSIT model is widely recommended as a framework for providing sexual information and support, allowing for the discussion of sexual changes at various levels of increasing intensity. The aim of the present study is to evaluate the early stages of the PLISSIT model by examining the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 98 publications
(130 reference statements)
0
32
0
2
Order By: Relevance
“…The PLISSIT model is one example of an approach providers can use to discuss sexuality and intimacy with their patients. 15,16 Our study has several limitations. It included a small number of patients at a single academic institution and thus may have limited applicability to other environments and locations.…”
Section: Discussionmentioning
confidence: 94%
“…The PLISSIT model is one example of an approach providers can use to discuss sexuality and intimacy with their patients. 15,16 Our study has several limitations. It included a small number of patients at a single academic institution and thus may have limited applicability to other environments and locations.…”
Section: Discussionmentioning
confidence: 94%
“…This model continues to be widely used to provide sexual education and as a method to illicit discussion about sexual health based on the different levels of the intervention (Perz & Ussher, 2015). Instructional methods were based on main chapter topics found in Models of Teaching (Joyce, Weil, & Calhoun, 2009).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…In our study, we found that a significant proportion of women with cervical cancer is sexually active at the beginning of treatment, however, they have significant sexual dysfunction, due to increased stress after the diagnosis or adverse symptoms related to the tumor [1]. The PLISSIT model which consists in four levels of intervention-Permission, Limited Information, Specific Suggestions and Intensive Therapyhas been widely suggested as an intervention to treat sexual dysfunction after cancer [3]. Kim et al notes that in Korea, programs based on the PLISSIT model have been successfully implemented in women with gynecological cancer [4,5].…”
mentioning
confidence: 78%